The Effectiveness of Vibrating Screen on the Composition of Feeds at PT KSP AGRO - Siregar, Ahdiat L; Hendra Saputra; Azhar Basyir Rantawi; Istianto Budhi Raharja; Rafael Billy; Kelvin Syahdan (Jurnal Inotera, 2026)
Vibrating screen is a filter unit that plays an important role in clarification stations because it functions to separate coarse impurities from crude oil so that the quality of the oil is improved and the oil loss can be minimized. The data used in this study is in the form of bait composition consisting of oil, water, and NOS in several observation periods. The data was then evaluated to determine the relationship between the variation in the composition of the feed and the effectiveness of the resulting filtering. The results of the study show that the effectiveness of vibrating screen tend to fluctuate in each observation period. Effectiveness increases when the oil content in the feed is higher, as the oil is more easily separated from impurities.